Research method for enhancing stable catalytic mechanism of activated carbon by using carbon black
Through the composite technology of carbon black and activated carbon, the high energy consumption and inactivation problems of catalysts during methane cracking and hydrogen production are solved, the stability and efficiency of the catalyst are improved, and the hydrogen production effect with low energy consumption and low emission is achieved.
Patent Information
- Application Number
- CN202411213279.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the methane cracking and hydrogen production process, existing catalysts have problems such as high energy consumption and carbon nanotube shedding, resulting in the damage to the catalyst structure. The activated carbon catalyst is rapidly deactivated, and the catalytic activity of carbon black is stable but the initial conversion rate is low.
Through the composite of carbon black and activated carbon, physical mixing, impregnation and co-precipitation methods, the uniform distribution of carbon black in activated carbon was improved, characterization analysis and catalytic performance testing were carried out, and activated carbon inactivation and self-enhancement of catalytic performance of carbon black were investigated. The mechanism of the mechanism of establishing a control mechanism to reduce the inactivation rate of activated carbon carriers.
It improves the efficiency of hydrogen production by methane cracking and the stability of the catalyst, extends the service life of activated carbon, and reduces energy consumption and emissions.
Smart Images

Figure CN119246757A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of clean energy, and in particular to a research method for utilizing carbon black to enhance the stable catalytic mechanism of activated carbon. Background Art
[0002] As the population increases, energy demand will continue to increase, and the development of efficient and clean energy is imperative. Hydrogen energy, as the most promising form of energy, has the huge advantages of high calorific value, no pollution, and renewable. Methane is the main component of natural gas and is the most commonly used raw material for large-scale industrial hydrogen production. Although natural gas reforming has been industrially applied and the technology is relatively mature, this method will cause a large amount of carbon dioxide emissions on the one hand, which is not conducive to greenhouse gas emission reduction; on the other hand, the reaction requires the absorption of a large amount of heat and has high energy consumption. Therefore, in recent years, methane cracking to produce hydrogen has been widely studied as a low-energy, low-emission hydrogen production method;
[0003] At present, the research focus of methane cracking to produce hydrogen is mainly concentrated on the development of efficient, easily available, low-cost and stable catalysts. Metal catalysts have high catalytic activity, good stability and high catalytic methane cracking conversion rate, but the cost of metal catalysts is high. In addition, metal catalysts will form carbon nanotubes during the catalytic process. These carbon nanotubes will push the catalytically active metal particles away from the carrier surface. The regeneration process usually uses steam to remove carbon deposits, which will cause the metal particles to fall off and the catalyst structure to be destroyed. Therefore, metal catalysts are difficult to regenerate.
[0004] Carbon-based catalysts do not have this problem. In the process of catalytic methane cracking, carbon-based catalysts do not generate metal carbonized products. Using high-temperature steam can remove carbon deposits generated on the surface and regenerate the catalyst, which greatly improves the utilization rate. In addition, carbon-based catalysts are inexpensive, have a wide source of raw materials, are resistant to high temperatures, and are resistant to sulfur and other toxic impurities. Among carbon-based catalysts, activated carbon and carbon black show broad application prospects, but there are also some problems that need to be improved. For example, although the activated carbon catalyst has high initial activity, it deactivates quickly and has too low activity in the later stage. The carbon black catalyst has stable catalytic activity but its initial catalytic conversion rate is low. Therefore, a research method for enhancing the catalytic mechanism of activated carbon by using carbon black is proposed. A comparative study is conducted on activated carbon and carbon black materials with different deactivation performances, to explore the mechanism of activated carbon deactivation and self-enhancement of carbon black catalytic performance, to establish a control mechanism to reduce the deactivation rate of activated carbon carriers, and to further improve the efficiency of methane catalytic cracking and hydrogen production. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] Therefore, the purpose of the present invention is to provide a research method for utilizing carbon black to enhance the stable catalytic mechanism of activated carbon, to conduct comparative studies on activated carbon and carbon black materials with different deactivation performances, to explore the mechanism of activated carbon deactivation and self-enhancement of carbon black catalytic performance, to establish a control mechanism to reduce the deactivation rate of activated carbon carriers, and to further improve the efficiency of methane catalytic cracking to produce hydrogen.
[0007] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:
[0008] A method for studying the mechanism of catalytic stability of activated carbon enhanced by carbon black comprises the following steps:
[0009] S1. Material preparation:
[0010] Selection and preparation of activated carbon: Select appropriate activated carbon as the catalyst matrix, and use activated carbon with high specific surface area and good pore structure;
[0011] Selection and preparation of carbon black: Select the appropriate carbon black variety, and choose carbon black with high surface area and high conductivity;
[0012] S2. Composite of carbon black and activated carbon:
[0013] Composite method:
[0014] Physical mixing: Mix carbon black and activated carbon in a certain proportion to obtain a composite catalyst through physical mixing;
[0015] Impregnation method: The activated carbon is immersed in a suspension of carbon black, and after a certain period of reaction, it is dried to obtain activated carbon enhanced with carbon black;
[0016] Co-precipitation method: precipitate carbon black particles on the surface of activated carbon to improve the uniform distribution of carbon black in the activated carbon;
[0017] S3. Characterization and analysis:
[0018] Specific surface area and pore structure: Use BET analysis to measure specific surface area and pore volume to understand the effect of carbon black on the pore structure of activated carbon;
[0019] Surface element analysis: Analyze the chemical state of surface elements through X-ray photoelectron spectroscopy to understand the effect of carbon black on the surface functional groups of activated carbon;
[0020] Microstructure analysis: Use scanning electron microscopy or transmission electron microscopy to observe the microstructure of the catalyst and the distribution of carbon black;
[0021] S4. Catalytic performance test:
[0022] Methane cracking reaction: At high temperature, such as 700-1000°C, methane cracking reaction is carried out to test the hydrogen yield and catalytic activity of the catalyst;
[0023] Stability test: Run the methane cracking reaction for a long time to detect the stability and deactivation of the catalyst.
[0024] As a preferred solution of the research method of using carbon black to enhance the catalytic mechanism of activated carbon stability described in the present invention, wherein: in step S2, the physical mixing of carbon black and activated carbon includes the following operating steps:
[0025] A1. Pretreatment:
[0026] Screening: Screen the carbon black and activated carbon separately to remove possible agglomerates and ensure the uniformity of the particles;
[0027] Drying: If the material is wet, it should be dried to avoid clumping during mixing;
[0028] A2. Mixing: Ball mill mixing: Put carbon black and activated carbon into the grinding tank of the ball mill in proportion, set appropriate grinding time and speed, and control the mixing time within 1-2h. After the operation is completed, take out the mixture and sieve it to ensure uniformity.
[0029] As a preferred solution of the research method of using carbon black to enhance the catalytic mechanism of activated carbon stability described in the present invention, wherein: in step S2, the impregnation and mixing of carbon black and activated carbon includes the following operating steps:
[0030] B1. Select and prepare materials:
[0031] Choose the right activated carbon and carbon black varieties;
[0032] Solution preparation: add carbon black to an appropriate amount of solvent, such as deionized water or an organic solvent, and use an ultrasonic oscillator to help disperse the carbon black;
[0033] B2. Impregnation:
[0034] Preparing the impregnation solution: preparing the carbon black suspension at the desired concentration, the concentration of carbon black in the suspension is adjusted according to the target loading;
[0035] Soaking activated carbon: Place the activated carbon in the impregnation liquid, making sure that the activated carbon is completely immersed in the liquid. The soaking time should be controlled between 1-8 hours, depending on the solubility of carbon black and the pore structure of the activated carbon.
[0036] B3. Stirring:
[0037] Use a magnetic stirrer or other stirring equipment to stir the impregnation liquid to ensure uniform dispersion of carbon black in the liquid. The stirring time is adjusted according to the actual situation in step B2, usually 1-2 hours, to avoid precipitation of carbon black.
[0038] As a preferred solution of the research method of using carbon black to enhance the catalytic mechanism of activated carbon stabilization described in the present invention, wherein: in step S2, the co-precipitation method of carbon black and activated carbon includes the following operating steps:
[0039] C1. Material preparation:
[0040] Select activated carbon with high specific surface area and good pore structure, and carbon black with high specific surface area and good dispersibility. If a carbon black precursor is used, prepare a corresponding chemical precursor solution, such as a carbon black precursor solution;
[0041] C2. Solution preparation:
[0042] Carbon black solution:
[0043] Dispersion: Add carbon black to an appropriate amount of solvent, such as deionized water or an organic solvent, and fully disperse the carbon black by ultrasonic treatment or stirring. The concentration of carbon black is adjusted according to actual needs, usually within the concentration range of 0.1-1%;
[0044] Activated carbon soaking solution:
[0045] The activated carbon is pretreated, washed and dried to remove surface impurities and increase its surface activity, and placed in a carbon black solution;
[0046] C3. Coprecipitation process:
[0047] Prepare precursor solution:
[0048] Dissolving: dissolving the carbon black precursor, such as the carbon source precursor, in an appropriate amount of solvent, usually deionized water or other suitable solvent, to form a uniform solution;
[0049] Mixing and settling:
[0050] Mixing: Add carbon black solution and activated carbon into the precursor solution together, ensuring thorough mixing;
[0051] Precipitation: By adjusting the precipitation conditions, such as pH value, temperature, and the addition of precipitants, the co-precipitation of carbon black and activated carbon is promoted. The precipitant can be an acid or a base.
[0052] C4, separation and washing:
[0053] Separation:
[0054] Use filters to separate the sediment from the liquid, and choose appropriate filter media to ensure the separation of carbon black and activated carbon;
[0055] Centrifugation:
[0056] If the sediment particles are small, a centrifuge can be used for separation to improve the separation efficiency;
[0057] Cleaning:
[0058] Wash the precipitate with deionized water or other appropriate solvent to remove residual substances in the solution. The washing step may need to be repeated several times until the washing solution becomes clear.
[0059] Dehydration: Dehydrate the washed sediment, using a centrifuge or a filter;
[0060] C5. Drying and post-processing:
[0061] dry:
[0062] Dry the separated precipitate in an oven. Usually dry at 100-120°C, and the drying time depends on the moisture content of the precipitate and the performance of the oven. Ensure complete drying to avoid moisture problems in subsequent processing;
[0063] Carbonization or reduction:
[0064] The dried composite material is heat treated to improve its stability and performance. Common heat treatment processes include carbonization, reduction or high temperature treatment.
[0065] As a preferred solution of the research method of utilizing carbon black to enhance the catalytic stability of activated carbon described in the present invention, step S3 includes the following steps:
[0066] N1. By adjusting the reaction time of activated carbon and carbon black, activated carbon and carbon black samples with different carbon deposit amounts at different times are collected;
[0067] N2. Perform multi-scale characterization tests such as scanning electron microscopy, TEM / HRTEM on the samples, use X-ray diffraction to analyze the crystallinity of carbon deposits, and observe the structural characteristics, lattice defects and dislocation characteristics of carbon deposits on activated carbon and carbon black catalysts at the micro-nano scale;
[0068] N3. Compare the morphological characteristics of carbon deposits at different times, observe the evolution of the size structure of carbon deposits on the surfaces of activated carbon and carbon black, and reveal the microscopic growth process of carbon deposits on the surfaces of activated carbon and carbon black;
[0069] N4. Based on the microstructural characteristics of carbon deposits and their growth process, combined with the evolution of catalytic reaction rate, the relationship between different carbon deposit morphologies and catalytic reaction rate is explored;
[0070] N5. Identify the boundary between the carbon deposit and the catalyst body, clarify the microscopic transition bonding characteristics between the two, analyze the reasons why the active sites produce different carbon deposition characteristics based on the microstructural characteristics of activated carbon, carbon black and the carbon deposits themselves, and explain the mechanism of activated carbon deactivation and self-enhancement of carbon black catalytic performance.
[0071] Compared with the prior art, the present invention has the following beneficial effects:
[0072] A comparative study was conducted on activated carbon and carbon black materials with different deactivation performances to explore the mechanism of activated carbon deactivation and self-enhancement of carbon black catalytic performance, establish a control mechanism to reduce the deactivation rate of activated carbon carriers, and further improve the efficiency of methane cracking to produce hydrogen and the stability of the catalyst by studying the catalytic performance scheme of carbon black enhanced activated carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the present invention will be described in detail below in combination with the accompanying drawings and detailed embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0074] Figure 1 Schematic diagram of the research steps of activated carbon deactivation and carbon black catalytic performance self-enhancement in the present invention;
[0075] Figure 2 It is a schematic diagram of the mechanism study process of activated carbon deactivation and self-enhancement of carbon black catalytic performance in the present invention. DETAILED DESCRIPTION
[0076] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0077] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0078] Secondly, the present invention is described in detail with reference to schematic diagrams. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.
[0079] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0080] The present invention provides a research method for utilizing carbon black to enhance the catalytic stability of activated carbon, comprising the following steps:
[0081] S1. Material preparation:
[0082] Selection and preparation of activated carbon: Select appropriate activated carbon as the catalyst matrix, and use activated carbon with high specific surface area and good pore structure;
[0083] Selection and preparation of carbon black: Select the appropriate carbon black variety, and choose carbon black with high surface area and high conductivity;
[0084] S2. Composite of carbon black and activated carbon:
[0085] Composite method:
[0086] Physical mixing: Mix carbon black and activated carbon in a certain proportion to obtain a composite catalyst through physical mixing;
[0087] Impregnation method: The activated carbon is immersed in a suspension of carbon black, and after a certain period of reaction, it is dried to obtain activated carbon enhanced with carbon black;
[0088] Co-precipitation method: precipitate carbon black particles on the surface of activated carbon to improve the uniform distribution of carbon black in the activated carbon;
[0089] S3. Characterization and analysis:
[0090] Specific surface area and pore structure: Use BET analysis to measure specific surface area and pore volume to understand the effect of carbon black on the pore structure of activated carbon;
[0091] Surface element analysis: Analyze the chemical state of surface elements through X-ray photoelectron spectroscopy to understand the effect of carbon black on the surface functional groups of activated carbon;
[0092] Microstructure analysis: Use scanning electron microscopy or transmission electron microscopy to observe the microstructure of the catalyst and the distribution of carbon black;
[0093] S4. Catalytic performance test:
[0094] Methane cracking reaction: At high temperature, such as 700-1000°C, methane cracking reaction is carried out to test the hydrogen yield and catalytic activity of the catalyst;
[0095] Stability test: Run the methane cracking reaction for a long time to detect the stability and deactivation of the catalyst.
[0096] In step S2, the physical mixing of carbon black and activated carbon includes the following steps:
[0097] A1. Pretreatment:
[0098] Screening: Screen the carbon black and activated carbon separately to remove possible agglomerates and ensure the uniformity of the particles;
[0099] Drying: If the material is wet, it should be dried to avoid clumping during mixing;
[0100] A2. Mixing: Ball mill mixing: Put carbon black and activated carbon into the grinding tank of the ball mill in proportion, set appropriate grinding time and speed, and control the mixing time within 1-2h. After the operation is completed, take out the mixture and sieve it to ensure uniformity.
[0101] In step S2, the impregnation and mixing of carbon black and activated carbon includes the following steps:
[0102] B1. Select and prepare materials:
[0103] Choose the right activated carbon and carbon black varieties;
[0104] Solution preparation: add carbon black to an appropriate amount of solvent, such as deionized water or an organic solvent, and use an ultrasonic oscillator to help disperse the carbon black;
[0105] B2. Impregnation:
[0106] Preparing the impregnation solution: preparing the carbon black suspension at the desired concentration, the concentration of carbon black in the suspension is adjusted according to the target loading;
[0107] Soaking activated carbon: Place the activated carbon in the impregnation liquid, making sure that the activated carbon is completely immersed in the liquid. The soaking time should be controlled between 1-8 hours, depending on the solubility of carbon black and the pore structure of the activated carbon.
[0108] B3. Stirring:
[0109] Use a magnetic stirrer or other stirring equipment to stir the impregnation liquid to ensure uniform dispersion of carbon black in the liquid. The stirring time is adjusted according to the actual situation in step B2, usually 1-2 hours, to avoid precipitation of carbon black.
[0110] In step S2, the carbon black and activated carbon co-precipitation method comprises the following steps:
[0111] C1. Material preparation:
[0112] Select activated carbon with high specific surface area and good pore structure, and carbon black with high specific surface area and good dispersibility. If a carbon black precursor is used, prepare a corresponding chemical precursor solution, such as a carbon black precursor solution;
[0113] C2. Solution preparation:
[0114] Carbon black solution:
[0115] Dispersion: Add carbon black to an appropriate amount of solvent, such as deionized water or an organic solvent, and fully disperse the carbon black by ultrasonic treatment or stirring. The concentration of carbon black is adjusted according to actual needs, usually within the concentration range of 0.1-1%;
[0116] Activated carbon soaking solution:
[0117] The activated carbon is pretreated, washed and dried to remove surface impurities and increase its surface activity, and placed in a carbon black solution;
[0118] C3. Coprecipitation process:
[0119] Prepare precursor solution:
[0120] Dissolving: dissolving the carbon black precursor, such as the carbon source precursor, in an appropriate amount of solvent, usually deionized water or other suitable solvent, to form a uniform solution;
[0121] Mixing and settling:
[0122] Mixing: Add carbon black solution and activated carbon into the precursor solution together, ensuring thorough mixing;
[0123] Precipitation: By adjusting the precipitation conditions, such as pH value, temperature, and the addition of precipitants, the co-precipitation of carbon black and activated carbon is promoted. The precipitant can be an acid or a base.
[0124] C4, separation and washing:
[0125] Separation:
[0126] Use filters to separate the sediment from the liquid, and choose appropriate filter media to ensure the separation of carbon black and activated carbon;
[0127] Centrifugation:
[0128] If the sediment particles are small, a centrifuge can be used for separation to improve the separation efficiency;
[0129] Cleaning:
[0130] Wash the precipitate with deionized water or other appropriate solvent to remove residual substances in the solution. The washing step may need to be repeated several times until the washing solution becomes clear.
[0131] Dehydration: Dehydrate the washed sediment, using a centrifuge or a filter;
[0132] C5. Drying and post-processing:
[0133] dry:
[0134] Dry the separated precipitate in an oven. Usually dry at 100-120°C, and the drying time depends on the moisture content of the precipitate and the performance of the oven. Ensure complete drying to avoid moisture problems in subsequent processing;
[0135] Carbonization or reduction:
[0136] The dried composite material is heat treated to improve its stability and performance. Common heat treatment processes include carbonization, reduction or high temperature treatment.
[0137] Step S3 includes the following steps:
[0138] N1. By adjusting the reaction time of activated carbon and carbon black, activated carbon and carbon black samples with different carbon deposit amounts at different times are collected;
[0139] N2. Perform multi-scale characterization tests such as scanning electron microscopy, TEM / HRTEM on the samples, use X-ray diffraction to analyze the crystallinity of carbon deposits, and observe the structural characteristics, lattice defects and dislocation characteristics of carbon deposits on activated carbon and carbon black catalysts at the micro-nano scale;
[0140] N3. Compare the morphological characteristics of carbon deposits at different times, observe the evolution of the size structure of carbon deposits on the surfaces of activated carbon and carbon black, and reveal the microscopic growth process of carbon deposits on the surfaces of activated carbon and carbon black;
[0141] N4. Based on the microstructural characteristics of carbon deposits and their growth process, combined with the evolution of catalytic reaction rate, the relationship between different carbon deposit morphologies and catalytic reaction rate is explored;
[0142] N5. Identify the boundary between the carbon deposit and the catalyst body, clarify the microscopic transition bonding characteristics between the two, analyze the reasons why the active sites produce different carbon deposition characteristics based on the microstructural characteristics of activated carbon, carbon black and the carbon deposits themselves, and explain the mechanism of activated carbon deactivation and self-enhancement of carbon black catalytic performance.
[0143] Although the present invention has been described above with reference to the embodiments, various modifications may be made thereto and parts thereof may be replaced by equivalents without departing from the scope of the present invention. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed in the present invention may be used in combination with each other in any manner, and the fact that these combinations are not exhaustively described in this specification is only for the sake of omitting space and saving resources. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A research method for utilizing carbon black to enhance the catalytic stability of activated carbon, characterized in that: The steps include: S1. Material preparation: Selection and preparation of activated carbon: Select appropriate activated carbon as the catalyst matrix, and use activated carbon with high specific surface area and good pore structure; Selection and preparation of carbon black: Select the appropriate carbon black variety, and choose carbon black with high surface area and high conductivity; S2. Composite of carbon black and activated carbon: Composite method: Physical mixing: Mix carbon black and activated carbon in a certain proportion to obtain a composite catalyst through physical mixing; Impregnation method: The activated carbon is immersed in a suspension of carbon black, and after a certain period of reaction, it is dried to obtain activated carbon enhanced with carbon black; Co-precipitation method: precipitate carbon black particles on the surface of activated carbon to improve the uniform distribution of carbon black in the activated carbon; S3. Characterization and analysis: Specific surface area and pore structure: Use BET analysis to measure specific surface area and pore volume to understand the effect of carbon black on the pore structure of activated carbon; Surface element analysis: Analyze the chemical state of surface elements through X-ray photoelectron spectroscopy to understand the effect of carbon black on the surface functional groups of activated carbon; Microstructure analysis: Use scanning electron microscopy or transmission electron microscopy to observe the microstructure of the catalyst and the distribution of carbon black; S4. Catalytic performance test: Methane cracking reaction: At high temperature, such as 700-1000°C, methane cracking reaction is carried out to test the hydrogen yield and catalytic activity of the catalyst; Stability test: Run the methane cracking reaction for a long time to detect the stability and deactivation of the catalyst.
2. The method for studying the mechanism of catalytic stability of activated carbon enhanced by carbon black according to claim 1, characterized in that: In step S2, the physical mixing of carbon black and activated carbon includes the following steps: A1. Pretreatment: Screening: Screen the carbon black and activated carbon separately to remove possible agglomerates and ensure the uniformity of the particles; Drying: If the material is wet, it should be dried to avoid clumping during mixing; A2. Mixing: Ball mill mixing: Put carbon black and activated carbon into the grinding tank of the ball mill in proportion, set appropriate grinding time and speed, and control the mixing time within 1-2h. After the operation is completed, take out the mixture and sieve it to ensure uniformity.
3. The method for studying the mechanism of catalytic stability of activated carbon enhanced by carbon black according to claim 2, characterized in that: In step S2, the impregnation and mixing of carbon black and activated carbon includes the following steps: B1. Select and prepare materials: Choose the right activated carbon and carbon black varieties; Solution preparation: add carbon black to an appropriate amount of solvent, such as deionized water or an organic solvent, and use an ultrasonic oscillator to help disperse the carbon black; B2. Impregnation: Preparing the impregnation solution: preparing the carbon black suspension at the desired concentration, the concentration of carbon black in the suspension is adjusted according to the target loading; Soaking activated carbon: Place the activated carbon in the impregnation liquid, making sure that the activated carbon is completely immersed in the liquid. The soaking time should be controlled between 1-8 hours, depending on the solubility of carbon black and the pore structure of the activated carbon. B3. Stirring: Use a magnetic stirrer or other stirring equipment to stir the impregnation liquid to ensure uniform dispersion of carbon black in the liquid. The stirring time is adjusted according to the actual situation in step B2, usually 1-2 hours, to avoid precipitation of carbon black.
4. The method for studying the mechanism of catalytic stability of activated carbon enhanced by carbon black according to claim 3, characterized in that: In step S2, the carbon black and activated carbon co-precipitation method comprises the following steps: C1. Material preparation: Select activated carbon with high specific surface area and good pore structure, and carbon black with high specific surface area and good dispersibility. If a carbon black precursor is used, prepare a corresponding chemical precursor solution, such as a carbon black precursor solution; C2. Solution preparation: Carbon black solution: Dispersion: Add carbon black to an appropriate amount of solvent, such as deionized water or an organic solvent, and fully disperse the carbon black by ultrasonic treatment or stirring. The concentration of carbon black is adjusted according to actual needs, usually within the concentration range of 0.1-1%; Activated carbon soaking solution: The activated carbon is pretreated, washed and dried to remove surface impurities and increase its surface activity, and placed in a carbon black solution; C3. Coprecipitation process: Prepare precursor solution: Dissolving: dissolving the carbon black precursor, such as the carbon source precursor, in an appropriate amount of solvent, usually deionized water or other suitable solvent, to form a uniform solution; Mixing and settling: Mixing: Add carbon black solution and activated carbon into the precursor solution together, ensuring thorough mixing; Precipitation: By adjusting the precipitation conditions, such as pH value, temperature, and the addition of precipitants, the co-precipitation of carbon black and activated carbon is promoted. The precipitant can be an acid or a base. C4, separation and washing: Separation: Use filters to separate the sediment from the liquid, and choose appropriate filter media to ensure the separation of carbon black and activated carbon; Centrifugation: If the sediment particles are small, a centrifuge can be used for separation to improve the separation efficiency; Cleaning: Wash the precipitate with deionized water or other appropriate solvent to remove residual substances in the solution. The washing step may need to be repeated several times until the washing solution becomes clear. Dehydration: Dehydrate the washed sediment, using a centrifuge or a filter; C5. Drying and post-processing: dry: Dry the separated precipitate in an oven. Usually dry at 100-120°C, and the drying time depends on the moisture content of the precipitate and the performance of the oven. Ensure complete drying to avoid moisture problems in subsequent processing; Carbonization or reduction: The dried composite material is heat treated to improve its stability and performance. Common heat treatment processes include carbonization, reduction or high temperature treatment.
5. The method for studying the mechanism of catalytic stability of activated carbon enhanced by carbon black according to claim 4, characterized in that: The step S3 comprises the following steps: N1. By adjusting the reaction time of activated carbon and carbon black, activated carbon and carbon black samples with different carbon deposit amounts at different times are collected; N2. Perform multi-scale characterization tests such as scanning electron microscopy, TEM / HRTEM on the samples, use X-ray diffraction to analyze the crystallinity of carbon deposits, and observe the structural characteristics, lattice defects and dislocation characteristics of carbon deposits on activated carbon and carbon black catalysts at the micro-nano scale; N3. Compare the morphological characteristics of carbon deposits at different times, observe the evolution of the size structure of carbon deposits on the surfaces of activated carbon and carbon black, and reveal the microscopic growth process of carbon deposits on the surfaces of activated carbon and carbon black; N4. Based on the microstructural characteristics of carbon deposits and their growth process, combined with the evolution of catalytic reaction rate, the relationship between different carbon deposit morphologies and catalytic reaction rate is explored; N5. Identify the boundary between the carbon deposit and the catalyst body, clarify the microscopic transition bonding characteristics between the two, analyze the reasons why the active sites produce different carbon deposition characteristics based on the microstructural characteristics of activated carbon, carbon black and the carbon deposits themselves, and explain the mechanism of activated carbon deactivation and self-enhancement of carbon black catalytic performance.